Structure of the Dospert: Is There Evidence for a General Risk Factor?. (5th April 2016) - Highhouse, Scott; Nye, Christopher D.; Zhang, Don C.; Rada, Thaddeus B.
Abstract: The Domain‐specific Risk‐taking scale was designed to assess risk taking in specific domains. This approach is unconventional in personality assessment but reflects conventional wisdom in the decision community that cross‐situational consistency in risk taking is more myth than reality. We applied bifactor analysis to a large sample ( n = 921) of responses to the Domain‐specific Risk Taking. Results showed that, in addition to domain‐specific facets, there does appear to be evidence for a general risk‐taking disposition. And this general appetite for risk appears to be useful for predicting real‐world outcomes. Copyright © 2016 John Wiley & Sons, Ltd.